PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN CONSUMER NON CYCLICALS PERIODE 2021-2024 - Beryl, Sharla Aurellia; Pramono, Hadi; Pratama, Bima Cinintya; Hapsari , Ira (Politeknik Negeri Ambon, 2026)
Introduction: This research aims to determine the impact of Financial Performance variables on Company Value with Managerial Ownership as a Moderating Variable in Consumer Non – Cyclicals Companies for the 2021-2024 Period. Methods: This study used secondary data from annual financial reports in a quantitative manner. The sample was chosen via purposeful sampling, yielding 178 observations. Using Stata software, multiple linear regression and Moderated Regression Analysis (MRA) were used to examine the data. Results: Previous study has not comprehensively tested the combination of Financial Performance, Company Value, and Managerial Ownership as moderating variables. The study's findings demonstrate that firm value is significantly impacted by financial performance as determined by ROA and ROE. The relationship between business value and financial performance does not depend of managerial ownership. Conclusion: Financial performance measured using ROA and ROE has a positive and significant impact on firm value. However managerial ownership cannot moderate this relationship, investors focus more on a company’s financial performance than managerial ownership structure when assessing a companySugesstion: This study suggests that Non-Cyclical Consumer companies prioritize improving financial performance to optimize ROA and ROE, as they have been shown to significantly impact firm value, while managerail ownership has not been able to strengthe this relationship. Future research is recommended to expand the observation period or add other variables to provide comprehensive results. Keywords: Financial Perfomance, Firm Value, Managerial Ownership